2022
DOI: 10.3390/educsci12110793
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking and Coding for Young Children: A Hybrid Approach to Link Unplugged and Plugged Activities

Abstract: In our increasingly technology-dependent society, the importance of promoting digital literacy (e.g., computational thinking, coding, and programming) has become a critical focus in the field of childhood education. While young children these days are routinely and extensively exposed to digital devices and tools, the efficacy of the methods for fostering digital skills in the early childhood classroom has not always been closely considered. This is particularly true in settings where early childhood educators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…Although this finding has not been discussed together with digital literacy skills and computational thinking self-efficacy in the literature, it was seen that there are similar results obtained when compared with different research findings. For example, Akiba (2022), George-Reyes et al (2021 and Menon et al (2020) found that 'having digital literacy skills affects the academic achievement of secondary school students together with their computational thinking skills. Therefore, digital literacy skills play an important role in computational thinking skills to achieve learning goals (Fagerlund et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this finding has not been discussed together with digital literacy skills and computational thinking self-efficacy in the literature, it was seen that there are similar results obtained when compared with different research findings. For example, Akiba (2022), George-Reyes et al (2021 and Menon et al (2020) found that 'having digital literacy skills affects the academic achievement of secondary school students together with their computational thinking skills. Therefore, digital literacy skills play an important role in computational thinking skills to achieve learning goals (Fagerlund et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be suggested that 21st-century skills such as problemsolving and digital literacy may affect computational thinking skills. To be able to use technology in education, it can be stated that having digital literacy and computational thinking skills, which are stated as two intertwined concepts, can be academically effective for middle school students (Menon et al, 2020;George-Reyes et al, 2021;Akiba, 2022). Therefore, it is thought that digital literacy skills can support computational thinking skills.…”
Section: Digital Literacy and Computational Thinkingmentioning
confidence: 99%
See 2 more Smart Citations